Antecedent Kinerja Pegawai di Universitas Muhammadiyah Sidoarjo - Mashudi Mashudi (Universitas Muhammadiyah Sidoarjo, 2014)
This research is conducted based on phenomenon that the employee performance at University of Muhammadiyah Sidoarjo is still not maximum. The indication is in the form of complaints issued by faculty members and students about cleanliness, parking system, and the queue length of administration and financial services. This study aims to determine the variables that most affect the employee performance. The method employed in this research is quantitative with the format of explanation research and survey. The data were collected through questionnaires spread to 90 employees that are included in the sample. Sampling was done by using simple random sampling technique. While the data analysis was performed using multiple linear regression analysis with SPSS (Statistical Program for Social Science) program version 10:01. The result of this research reveals that compensation is the most decisive variable in determining the employee performance, followed by sequential organizational culture and human resource capability.